Blindsight - Watts, Peter, 1958- (Watts, Peter, 1958- Firefall, 2020)
Two months after the Earth is taken over by an alien species, a space probe detects a faint signal from the edge of the solar system and attempts to make contact, despite the dangers the signal hints at, relying on a linguist with multiple personalities to make the first contact and attempt a peace agreement.